Quantification of Radiological Hazards Associated with Natural Radionuclides in Rock Samples from Al-Meshal Region, Libya - M. Al-Abrdi, Asma; M. Ali, Jemila; A. Abd-Ahamid, Mabrouka (Scientific Journal of University of Benghazi, 2025)
The specific activity concentrations of primordial radionuclides in eight samples of rock collected from specific locations in Al-Meshal, Al-Gabal Al-Akhdar region, Libya, were measured using a1gamma-ray spectrometer system with a sodium iodide detector. The results revealed that the specific activity concentrations of 226Ra, 238U, and 232Th in the analyzed samples were higher than their respective established permissible levels. Conversely, the specific activity concentrations of 40K in all rock samples were found to be below the permissible limit. The assessment of the radiological1hazard parameters, including radium equivalent activity, internal and external hazard1indices, and representative level index, indicated values were mostly within recommended world limits. However, for two specific samples, RE1 and RW2, the representative level index and internal hazard index values were higher than the recommended world value. Although the radiological investigation indicates no immediate acute health hazard to the area’s population, there is a need to consider the long-term health effects related to low-level exposure to radiation.